Forest elephant density and distribution in the southern part of National Park Campo-Ma'an, Cameroon - Patricia Bekhuis; Herbert Prins (Pachyderm)
A dung count based 8 month survey during 2000-2001, undertaken in the southern part of Campo Ma'an NP in southwest Cameroon, suggests this area supports a high density of forest elephant. The elephant density was calculated to be 0.8 per sq km which is higher than known population densities in the region. 'No seasonsl differences in density were detected, nor were densities site dependent.' The results suggest the elephant population in this vicinity may losing range, and may literally be beginning to become compressed or trapped within the Park